(untitled) - Rose, Margaret (Indianapolis, IN, 2007)
This guide is more than just a listing of names — each entry contains variant spellings as well as the name's meaning, history, and derivations.
Keywords: Names, Personal,Tên, cá nhân; Dictionaries,Từ điển